ANALYSIS OF BUSINESS ECOSYSTEMS IN THE CONTEXT OF CREATIVE INDUSTRIES DEVELOPMENT - PROKOPENKO, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the concept of business ecosystems to identify the functioning mechanisms of these environments in the context of creative industries. The study suggests how marketing strategies and multiplier marketing tools can be effectively used to support and develop creative industries. The concepts of business and creative business ecosystems are examined by analyzing their characteristics, dynamics, and contributions to economic and cultural development. Business ecosystems are characterized by symbiotic relationships among economic participants, promoting mutual benefit and creating a supportive structure for collaboration and competition. In contrast, creative business ecosystems specifically focus on industries that produce goods and services based on cultural, artistic, or creative content. This includes sectors such as music, film, fashion, and digital media. The concept aims to expand traditional business ecosystem theory by incorporating elements of creativity and innovation as central to economic efficiency and competitive advantage in the context of creative industries. The research findings are valuable for policy development in the creative industries. They offer marketing tools for applying marketing multipliers as instruments for supporting the sustainable development of creative ecosystems and enhancing their innovation capacity.